THE DHAMMAYUTTIKA NIKĀYA (MAHĀYIN GAING) IN MON STATE, MYANMAR: A CRITICAL STUDY OF ITS HISTORICAL BACKGROUND AND IMPACT - Obhāsa, Ven. (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2024)
This research aims to critically examine the historical background of Dhammayuttika Nikāya in Mon State, Myanmar, and its impact in Buddhism there. The Dhammayuttika Nikāya was founded by King Mongkut of Thailand in the 19th century and expanded under King Chulalongkorn’s reforms, which led to regional resistance in Northern and Northeastern Thailand. The Nikāya also spread to Cambodia and Myanmar. In Myanmar, the Dhammayuttika Nikāya, known locally as the Mahāyin Gaing, was established in 1874 with minimal resistance. This research examines the lineage of the Nikāya's leaders, their ordination practices, and their monastic education. It further explores the social and historical connections between the Dhammayuttika Nikāya and other Nikāyas, and assesses the impact of the Dhammayuttika Nikāya's Buddhist text recitation ceremonies and the Chaungzon monastic examination. Employing a qualitative methodology with a library approach, this study analyzes primary sources such as Buddhist scriptures and secondary sources including scholarly writings, journals and articles, to show the Dhammayuttika Nikāya's contributions for propagation of Buddhism. This research contributes an in-depth understanding on the historical background and impacts of the Dhammayuttika Nikāya or Mahāyin Gaing in Mon State of Myanmar.